Orientação espiritual e ideação suicida entre usuários de substâncias psicoativas - Cruz, Jefferson Pereira Maciel da (2021)
Objective: To compare the relationship between spiritual orientation and suicidal ideation, according to the use of psychoactive substances, by people in rehabilitation process. Method: Cross-sectional, analytical study, with users of psychoactive substances in three institutions in southeastern Brazil, aged 18 years or older, of both genders. We applied a structured interview with sociodemographic information; a screening test for involvement with alcohol, tobacco, and other drugs; a Brazilian version of the Spirituality Self Rating Scale, and Beck's Suicidal Ideation Scale. For the analysis, descriptive statistics of the sociodemographic data were used, and the means of the groups were compared using the Kruskal-Wallis and Mann-Whitney tests. A 5% significance level was adopted. Results: Ninety-seven individuals participated in the study. The predominant sociodemographic characteristics were: male (91.8%), mean age 44 years, single (63.9%), and catholic (37.1%). Substance use screening identified higher frequency of probable dependence for alcohol, marijuana, and cocaine. When comparing the relationship between spiritual orientation and suicidal ideation, there were differences between the groups, with significant results for alcohol and marijuana users. In both groups, the highest levels of importance of spirituality were detected among heavy users, however, the risk of suicide was increased in the category of probable dependents. Conclusion: The scientific literature mostly evidences spirituality as a protective factor for suicidal behavior, while substance use tends to be a risk factor. This study, in turn, by recruiting people in the rehabilitation process, found that there may be some specificity of these relationships by focusing on users of different substances. Thus, new studies investigating the relationship between spirituality, suicide risk, and substance use in its diversity (type of drug, pattern, polyuse) and stages of readiness to change consumption are essential to generate evidence capable of contributing to the improvement of unique therapeutic projects, both in Primary Care and in specialized care.